Groundwater isotopic variations in a uranium mining site: subsidies for contamination studies - Valeska Peres de Araújo; Guilherme Augusto Nascimento Sobrinho; Leticia Deloque Freitas; Mariza Ramalho Franklin (Brazilian Journal of Radiation Sciences)
The Caetité Experimental Basin (CEB), located in the semi-arid region of Northeastern Brazil, faces not only the challenges associated with water scarcity but also the potential contamination processes due to mining activity. The only active uranium production center in Brazil (URA) is located in this watershed and the sustainability of mining and milling operations, as well as the survival of the local community, is highly dependent on the availability of groundwater resources. This paper analyzes the stable isotopes variation of Deuterium (2H) and Oxygen-18 (18O) in CEB’s groundwater to investigate its dynamics and mixing of water sources as part of initial efforts to characterize the hydrogeology of this area for future contamination and recharge studies. Measurements of δ2H, δ18O, total dissolved solids (TDS), pH, and electrical conductivity (EC) were carried out in water samples from 28 wells. A total of 102 groundwater samples were analyzed during the dry and wet seasons from 2012 to 2014. All the groundwater samples plotted below the local meteoric line toward more enriched δ18O values, an indicative of evaporation process. 2H and 18O data suggests that the main source of groundwater recharge is local precipitation and there is no mixing of infiltrating rainwater with older groundwater. These results provide evidence that the aquifer system in the CEB has a relatively fast turnover time, which contribute to the vulnerability of the aquifer to contamination. These findings are corroborated by the low TDS and EC values indicative of short time in water-rock interaction.